Adsorption and chemisorption of galactose oxidase on silica surface - Kondakova, L.V.; Yanishpolskii, V.V.; Tertykh, V.A. (Поверхность, 2002)
Experience accumulated over a number of years in developing of methods of immobilization of galactose oxidase from Fusarium graminearum on parent and modified silica matrices is analyzed. Sturdy adsorption of galactose oxidase on silica surface was observed, such heterogeneous specimens possessed by enhanced biocatalyst stability and activity as compared with enzyme solutions. Covalent immobilization of galactose oxidase was carried out on the amine-containing silicas activated by 2,4-tolylene diisocyanate and cyanuric chloride. It was also shown that in the presence of the substrate (galactose) enzyme chemisorption takes place on the surface on aminecontaining silica matrices. Immobilized preparations were successfully applied for analytical determination of galactose-containing carbohydrates (galactose, lactose, raffinose) in complex mixtures.